Model of Tsunami Mitigation and Evacuation Routes in Pancer Banyuwangi - Trisnawati Trisnawati; Surjono Surjono; Luchman Hakiem (Jurnal Penelitian Pendidikan IPA, 2024)
Banyuwangi has the largest tsunami disaster risk in East Java, about 45,305 affected people, Rp. 160,886,000,- for the risk of physical losses, Rp. 106,414,000,- for the risk of economic losses and 84 ha of environmental losses (BNPB, 2023). In addition, according to historical data, Banyuwangi was hit by tsunami on June 9, 1994 with magnitude of 7.8 which caused a maximum run up of 14.0 m and killed 238 lives (BNPB, 2023). Also based on Undang- undang No. 24 Tahun 2007 concerning Disaster Management, Indonesia should have preventive and mitigation measures for tsunami disasters both before and after as an effort to reduce the disaster risk (Putra, 2009) . Tsunami modeling in southern Java using COMCOT v1.7 as tsunami worst case scenario in Banyuwangi is the first step for mitigation. The initial results of COMCOT were then used for preparing tsunami disaster evacuation route planning based on the Tsunami Natural Disaster Evacuation Route Planning Guidelines, Dirjen Bina Marga, 2023. The final step is validation/routing survey of the 8 (eight) routes that have been determined. 2 (two) of the 8 (eight) routes fulfill the guidelines for planning tsunami mitigation routes. However, all routes can be considered due to the distribution of settlements, the number of affected residents and the number of routes needed